Anomalous transport of transversely accelerated ions in lower hybrid cavities - Azarenkov, N.A.; Chibisov, A.D.; Chibisov, D.V. (Вопросы атомной науки и техники, 2020)
The transport of particles and heat for transversely accelerated ions in lower hybrid cavities due to drift turbulence is investigated. The transport equations for the conditions of lower hybrid cavities are obtained. It is shown that the anomalous transport of particles and heat across the geomagnetic field in the lower hybrid cavities is caused to the scattering of ions by random pulsations of drift turbulence. It was found that the diffusion and thermal diffusion of accelerated ions in the cavity occurs in a time comparable to the time of filling the cavity with the back ground plasma. Досліджено перенесення частинок і тепла для поперечно прискорених іонів є нижньогібридних порожнинах у результаті розвитку дрейфової турбулентності. Отримано рівняння переносу для умов нижньогібридних порожнин. Показано, що аномальне перенесення часток і тепла поперек геомагнітного поля в нижньогібридних порожнинах обумовлене розсіюванням іонів на випадкових пульсаціях дрейфової турбулентності. Встановлено, що дифузія та термодифузія прискорених іонів у порожнині відбуваються за час, порівнянний з часом заповнення порожнини навколишньою плазмою. Исследован перенос частиц и тепла для поперечно ускоренных ионов в нижнегибридных полостях в результате развития дрейфовой турбулентности. Получены уравнения переноса для условий нижнегибридных полостей. Показано, что аномальный перенос частиц и тепла поперек геомагнитного поля в нижнегибридных полостях обусловлен рассеянием ионов на случайных пульсациях дрейфовой турбулентности. Установлено, что диффузия и термодиффузия ускоренных ионов в полости происходят за время, сравнимое со временем заполнения полости окружающей плазмой.